1985
DOI: 10.1159/000118217
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Experience with Lithium in Childhood Aggressivity

Abstract: An account is given of the therapeutic experience with lithium in childhood hyperaggressivity. In 13 cases of the hospitalized l7children between 3 and 12 years of age significant rehabilitation was achieved. Their sociability and ability to adapt themselves to the environment improved to a tolerable level. During treatment, no irreversible side effects were observed. It is recommended that the treatment should be performed either at a child psychiatric unit or by a psychiatrist with adequate experiences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Lithium carbonate, an alkali metal that enhances serotonergic activity in the brain has also yielded mixed results in studies on its efficacy in the treatment of children and adolescents with CD. Some studies reported low to high success rates in treating CD in children with lithium carbonate (e.g., Campbell et aI., 1984;Malone, Luebert, Pena-Ariet, Biesecker, & Delaney, 1994;Vetro, Szentistvanyi, Pallag, & Szilard, 1985). Treatment of CD in children with lithium carbonate was also associated with non-impairment of cognitive functions (Platt, Campbell, Green, & Grega, 1984).…”
Section: Neuroleptics and CDmentioning
confidence: 99%
“…Lithium carbonate, an alkali metal that enhances serotonergic activity in the brain has also yielded mixed results in studies on its efficacy in the treatment of children and adolescents with CD. Some studies reported low to high success rates in treating CD in children with lithium carbonate (e.g., Campbell et aI., 1984;Malone, Luebert, Pena-Ariet, Biesecker, & Delaney, 1994;Vetro, Szentistvanyi, Pallag, & Szilard, 1985). Treatment of CD in children with lithium carbonate was also associated with non-impairment of cognitive functions (Platt, Campbell, Green, & Grega, 1984).…”
Section: Neuroleptics and CDmentioning
confidence: 99%
“…There is a growing number of case reports and open trials suggesting that lithium may be an effective treatment for aggressive behavior in children and adolescents (e.g. DeLong & Aldershof, 1987;Vetro, Szentistvanyi, Pallag, Vargha & Szilard, 1985), but controlled studies are limited. Campbell et ai (1984) found lithium to be highly superior to placebo in suppressing aggressive behavior in hospitalized prepubertal children with conduct disorder.…”
Section: Efficacy Aggressionmentioning
confidence: 99%